Oesophageal secretions reveal local food‐specific antibody responses in eosinophilic oesophagitis. Issue 9 (20th September 2022) - Pyne, Ashley L.; Hazel, Mark W.; Uchida, Amiko M.; Qeadan, Fares; Jordan, Kristine C.; Holman, Amy; Harward, Brinnlie; Gleich, Gerald J.; Peterson, Kathryn A.
Summary: Background: Eosinophilic oesophagitis (EoE) is associated with elevated IgG4 in oesophageal tissue and serum. Previously, we showed brush‐collected oesophageal secretions of EoE patients contained food antigen‐specific antibodies IgA and IgG4. It is unknown whether other food‐specific antibodies are present along the surface of the oesophagus in EoE. Aim: To identify whether immunoglobulins other than IgG4 and food‐specific antibodies are elevated along the oesophageal mucosal surface in oesophageal secretions in EoE patients Methods: Concentrations of total IgA, IgG1, IgG2, IgG3, IgG4, IgM and IgE were measured in oesophageal secretions from patients with active ( n  = 19) and inactive EoE ( n  = 9), and non‐EoE controls ( n  = 10). Food‐specific antibodies were measured using beads coupled to protein components from dairy, wheat and egg. Total immunoglobulin and cytokine and chemokine concentrations were measured in serum, saliva and oesophageal secretions of four patients with active EoE. Results: Oesophageal secretions have a unique immune profile. Patients with active EoE had elevated IgG2, IgG4 and IgM concentrations in oesophageal secretions compared to those with inactive EoE. Food‐specific IgG1, IgG2, IgG4 and IgM were significantly increased in patients with active EoE compared to inactive EoE and non‐EoE patients. Furthermore, active patients with a known dairy trigger display higher dairy‐specific IgG1, IgG2, IgG4, IgM, IgA and IgE. Conclusions: There is a distinct localised profile of immunoglobulins and food‐specific antibodies found within oesophageal secretions in EoE. These findings expand our knowledge about the currently identified immune responses in EoE and suggest possible roles for multiple immunoglobulins and food‐specific antibodies in the pathophysiology of EoE. Abstract : Oesophageal secretions show a unique immune profile with elevated food‐specific antibodies in patients with active EoE.